Eventos adversos relacionados a medicamentos envolvendo opioides no Brasil. - Gabriela de Paula Guimarães Rodrigues (2023)
The use of opioids worldwide is an epidemic, with adverse drug-related events (ADE) involving this class of drugs being frequent, including those with serious outcomes, including deaths. Opioids are potentially dangerous medications, and, despite not being among the most used analgesics in Brazil, they are the second class of medications most used in a non-prescribed or different way than prescribed according to the National Drug Use Survey, and may be related to considerable damage. However, to the authors' knowledge, studies describing the occurrence of ADEs involving opioids in Brazil do not exist. This work aims to describe suspected ADEs involving opioid medications reported in the VigiMed system of the National Health Surveillance Agency (Anvisa). To this end, a descriptive study was carried out based on notifications made between 2018 and 2023, relating to at least one opioid medication. All data comes from the VigiMed primary database available in Anvisa's open pharmacovigilance data area. Reports of suspected ADEs were described according to the month of notification, reporting source and patient involved. For each notification, more than one reaction may be linked, and these are also described according to the type of reaction, outcome and severity. Opioids suspected of being involved in the reactions have also been described. 9,532 suspected ADEs involving opioids were reported in the period evaluated, representing 5.9% of total notifications. The majority of notifications came from the southeast (46.5%) and south (13.3%) regions and had “health services” (n=7,103; 74.5%) as the most common entry type. frequent and at least one pharmacist acted as notifier for the majority of notifications (67.5%; n=6,436). An average of 183.3 notifications per month was observed, and the majority of suspected ADEs involving opioids were female (61.6%; n=5,866), adults (52.5%; n=5,004) and elderly people. (19.1%, n=1,824). A total of 17,738 reactions involving opioids were observed and a predominance of these were related to cutaneous and subcutaneous tissue disorders in a total of 10,670 opioids supposedly involved in ADE. From this study, it was possible to analyze ADEs involving opioids, which demonstrated a considerable and increasing frequency, contrary to the decrease in use of the class in Brazil. This demonstrates that use must be properly monitored in the national context, preventing inappropriate use of this class.